Professional socialization: an analytical definition - Sadeghi Avval Shahr, Homa (J Med Ethics Hist Med, 2019)
Professional socialization is defined as a process through which a person becomes a legitimate member of a professional society. This will have a great impact on an individual’s professional conduct and morality. The aim of this study was to clarify this concept and reduce the ambiguities around it. This was a qualitative research through which the concept of professional socialization was analyzed using Walker and Avant’s eight-step approach. The review of literature for this concept was done using electronic database without any time limitation. The overall search produced about 780 articles, and after reviewing these articles, 21 were selected purposefully. Based on concept analysis, we propose the following analytical definition: Professional socialization is a nonlinear, continuous, interactive, transformative, personal, psychosocial and self-reinforcing process that is formed through internalization of the specific culture of a professional community, and can be affected by individual, organizational and interactional factors. This definition is in accordance with the interactionism perspective. Existence of a particular profession and getting involved in a community of practice are the antecedents of this process, and formation of professional identity and professional development are its consequences. A case model, as well as borderline and related cases, has been introduced for this concept. The results of this study can be used to design useful educational interventions to conduct and facilitate the process.